2020
DOI: 10.22271/chemi.2020.v8.i5c.10294
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between compaction levels (bulk density) and chemical properties of different textured soil

Abstract: The investigation entitled "Study of relationship between compaction level (bulk density) and chemical properties of different textured soil" was carried out using various research materials and analytical techniques during 2017-18 at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…According to Belayneh, Yirgu & Tsegaye (2019) , high BD negatively affected soil nutrients due to decreased soil biological and biochemical processes, resulting in reduced soil fertility. A similar result has been reported by Singh et al (2020) . They indicated a negative correlation between BD and soil nutrients.…”
Section: Discussionsupporting
confidence: 91%
“…According to Belayneh, Yirgu & Tsegaye (2019) , high BD negatively affected soil nutrients due to decreased soil biological and biochemical processes, resulting in reduced soil fertility. A similar result has been reported by Singh et al (2020) . They indicated a negative correlation between BD and soil nutrients.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, bulk density was positively correlated to pH-water. This may be explained by the soil compaction decreases porosity and reduction of organic matter in steeper slope [40]. Conversely, bulk density was negatively correlated to soil organic matter, confirming some researches that revealed the importance of organic carbon in soil aggregation, which decreases bulk density [41].…”
Section: Discussionsupporting
confidence: 64%
“…This is because conventional tillage can result in the loss of soil organic matter and nutrients, including micro-nutrients. Conventional tillage systems can lead to compaction of soils, resulting to increased soil bulk density which can reduce soil aeration and water infiltration, limiting zinc availability [ 37 ]. Singh et al [ 37 ] reported significant and strong negative correlations between soil bulk density and soil zinc availability (r = - 0.925–0.929) under loamy sand, sandy loam and sandy clay loam soils.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional tillage systems can lead to compaction of soils, resulting to increased soil bulk density which can reduce soil aeration and water infiltration, limiting zinc availability [ 37 ]. Singh et al [ 37 ] reported significant and strong negative correlations between soil bulk density and soil zinc availability (r = - 0.925–0.929) under loamy sand, sandy loam and sandy clay loam soils. In addition, high negative correlations were also detected between soil bulk density and soil Iron (r = −0.931 -0.981) for the same soil types [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation